Next-Generation Computationally Designed Influenza Hemagglutinin Vaccines Protect against H5Nx Virus Infections - Ivette A. Nuñez (MDPI AG, 2021)
H5N1 COBRA hemagglutinin (HA) sequences, termed human COBRA-2 HA, were constructed through layering of HA sequences from viruses isolated from humans collected between 2004–2007 using only clade 2 strains. These COBRA HA proteins, when expressed on the surface of virus-like particles (VLP), elicited protective immune responses in mice, ferrets, and non-human primates. However, these vaccines were not as effective at inducing neutralizing antibodies against newly circulating viruses. Therefore, COBRA HA-based vaccines were updated in order to elicit protective antibodies against the current circulating clades of H5Nx viruses. Next-generation COBRA HA vaccines were designed to encompass the newly emerging viruses circulating in wild avian populations. HA amino acid sequences from avian and human H5 influenza viruses isolated between 2011–2017 were downloaded from the GISAID (Global Initiative on Sharing All Influenza Data). Mice were vaccinated with H5 COBRA rHA that elicited antibodies with hemagglutinin inhibition (HAI) activity against H5Nx viruses from five clades. The H5 COBRA rHA vaccine, termed IAN8, elicited protective immune responses against mice challenged with A/Sichuan/26621/2014 and A/Vietnam/1203/2004. This vaccine elicited antibodies with HAI activity against viruses from clades 2.2, 2.3.2.1, 2.3.4.2, 2.2.1 and 2.2.2. Lungs from vaccinated mice had decreased viral titers and the levels of cellular infiltration in mice vaccinated with IAN-8 rHA were similar to mice vaccinated with wild-type HA comparator vaccines or mock vaccinated controls. Overall, these next-generation H5 COBRA HA vaccines elicited protective antibodies against both historical H5Nx influenza viruses, as well as currently circulating clades of H5N1, H5N6, and H5N8 influenza viruses.